Recent Advances in the Management of Pediatric Intestinal Failure - Chan-Fai Chan; Tzee-Chung Wu (Pediatrics and Neonatology)
Intestinal failure is a chronic condition in which the intestinal tract has lost most of its function. Prognosis depends on the severity and underlying etiologies. Although many patients survive under parenteral nutrition support, they often suffer from fatal complications such as progressive cholestasis and frequent sepsis. In addition, to decide the proper time to refer selected patients to bowel transplantation remains difficult. A noninvasive biomarker developed to evaluate functional enterocyte mass and the extent of intestinal adaptation is plasma citrulline level. It is shown that serum citrulline correlates with small bowel length, oral tolerance, and parenteral nutrition dependency. Recent evidence has revealed that the use of fish oil containing lipid emulsions to substitute traditional soybean-based formula may reverse a patient's cholestasis and improve lipid profiles. A new method used to prevent catheter-related bloodstream infection is ethanol lock therapy. With both antimicrobial and fibrinolytic activities, studies have shown that ethanol locks can effectively decrease catheter infection and replacement rate with no known resistance reported. As part of intestinal rehabilitation, auxiliary surgeries such as longitudinal intestinal lengthening and tailoring, serial transverse enteroplasty, and tapering enteroplasty can be beneficial for selected patients before bridging to bowel transplantation. With the introduction of these new medical and surgical modalities, patients with intestinal failure are having better outcomes than in the past.